The longing for everything: hellenistic models of universal kingship (Argos, 2023)
The pretension of a universal dominion expressed by several Hellenistic kings has recently been reconsidered; currently, it is regarded not as mere propaganda, but as a central and pressing trait of Hellenistic kingship. This work explores some models of monarchy that contributed to fashion the idea of universal kingship by analyzing both the influence of Near Eastern archetypes and the reception of Alexander the Great’s image. I propose that it was through these models that this “the longing for everything” was defined and shaped.
Keywords: Universalism; Kingship; Hellenism